2013
DOI: 10.1074/jbc.m113.490474
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of BAR Domain-containing Proteins in Regulating Vesicle Release Catalyzed by the GTPase, Dynamin-2

Abstract: Background: Membrane curvature generation is essential for dynamin-2-catalyzed membrane fission and vesicle release. Results: Dynamin-2 binding partners with curvature generating activity differentially regulate the assembly, GTPase, and fission activities of dynamin-2. Conclusion: Dynamin-2 partners display complex patterns of regulation. Significance: The distinct functional interactions between dynamin-2 and its binding partners position them to contribute to the spatio-temporal regulation of clathrin-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 64 publications
9
76
0
Order By: Relevance
“…Moreover, we also found that, in contrast to what has been observed for other members of the dynamin family (48,66,67), Drp1 bound to both flat and curved membranes in the absence of nucleotides. This is unexpected because curvature sensing is believed to be a key property of dynamin proteins, and it suggests a fundamentally different mechanism of action for Drp1.…”
Section: Discussionmentioning
confidence: 41%
“…Moreover, we also found that, in contrast to what has been observed for other members of the dynamin family (48,66,67), Drp1 bound to both flat and curved membranes in the absence of nucleotides. This is unexpected because curvature sensing is believed to be a key property of dynamin proteins, and it suggests a fundamentally different mechanism of action for Drp1.…”
Section: Discussionmentioning
confidence: 41%
“…In vitro, addition of only small ENTH domains containing AH to lipid bilayers reproduces the whole sequence of membrane transformations leading to fission of vesicles (Boucrot et al, 2012;Neumann and Schmid, 2013). However, in cells, AH generally acts in the context of a large protein complex, such as COPI and II, that arranges multiple AHs in space.…”
Section: Molecular Geometry and Fissionmentioning
confidence: 97%
“…They include COPI and COPII complexes (Bremser et al, 1999;Matsuoka et al, 1998;Pucadyil and Schmid, 2009), dynamin-1 (Roux et al, 2006;Sweitzer and Hinshaw, 1998) and 2 (Liu et al, 2011), the endocytic proteins epsin and its ENTH domain (Boucrot et al, 2012;Neumann and Schmid, 2013), amphiphysin, endophylin A1 and A3 and their N-BAR domains (Boucrot et al, 2012;Gallop et al, 2006;Peter et al, 2004). These proteins and their domains universally contain limited membrane-inserting parts, which are often described as "wedges" driven into the lipid monolayer by hydrophobic and electrostatic forces (Blood and Voth, 2006;Drin and Antonny, 2010;Zimmerberg and Kozlov, 2006).…”
Section: Molecular Geometry and Fissionmentioning
confidence: 98%
“…However, many questions remain concerning the mechanism of dynamin function and the roles of the numerous binding partners of dynamin including membrane curvature sensing/inducing BAR domain proteins such as amphiphysin and endophilin (Milosevic et al 2011;Meinecke et al 2013;Neumann and Schmid 2013) and proteins involved in actin polymerization/depolymerization (reviewed in Menon and Schafer 2013). Moreover, dynamin can also affect the earlier stages of CCP growth and invagination, although the precise mechanism by which it does so remains obscure (Loerke et al 2009;Mettlen et al 2009).…”
Section: Membrane Scissionmentioning
confidence: 99%